MAP3K8 Is a Prognostic Biomarker and Correlated With Immune Response in Glioma - Ren, Jing; Xu, Yixin; Liu, Jia; Wu, Sicheng; Zhang, Ruihan; Cao, Haowei; Sun, Jinmin (Frontiers in Molecular Biosciences, 2021)
MAP3K8 is a serine/threonine kinase that is widely expressed in immune cells, non-immune cells, and many tumor types. The expression, clinical significance, biological role, and the underlying molecular mechanisms of MAP3K8 in glioma have not been investigated yet. Here, we discovered that MAP3K8 was aberrantly overexpressed in glioma and correlated with poor clinicopathological features of glioma by analysis on different datasets and immunohistochemistry staining. MAP3K8 is an independent prognostic indicator and significantly correlates with the progression of glioma. We also performed the function and pathway enrichment analysis of MAP3K8 in glioma to explore its biological functions and underlying molecular mechanisms in glioma. MAP3K8 co-expressed genes were mainly enriched in immune-related biological processes such as neutrophil activation, leukocyte migration, neutrophil-mediated immunity, lymphocyte-mediated immunity, T-cell activation, leukocyte cell–cell adhesion, regulation of leukocyte cell–cell adhesion, B-cell-mediated immunity, myeloid cell differentiation, and regulation of cell–cell adhesion. Single-cell RNA sequencing data and immunohistochemistry analysis demonstrated that MAP3K8 is expressed in malignant and immune cells and mainly enriched in the microglia/macrophage cells of glioma. The expression of MAP3K8 was positively correlated with immune infiltration, including effector memory CD4+ T cells, plasmacytoid dendritic cells, neutrophils, myeloid dendritic cells, mast cells, and macrophage in glioma. Further correlation analysis demonstrated that a series of inhibitory immune checkpoint molecules, chemokines, and chemokine receptors was positively correlated with the expression of MAP3K8. MAP3K8 might play an essential role in tumor immunity, and inhibition of MPA3K8 is a plausible strategy for glioma immunotherapy.